2016
DOI: 10.1021/acs.jmedchem.6b00125
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptor Antagonist Dependent upon Transmembrane AMPA Receptor Regulatory Protein (TARP) γ-8

Abstract: Transmembrane AMPA receptor regulatory proteins (TARPs) are a family of scaffolding proteins that regulate AMPA receptor trafficking and function. TARP γ-8 is one member of this family and is highly expressed within the hippocampus relative to the cerebellum. A selective TARP γ-8-dependent AMPA receptor antagonist (TDAA) is an innovative approach to modulate AMPA receptors in specific brain regions to potentially increase the therapeutic index relative to known non-TARP-dependent AMPA antagonists. We describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…It is noteworthy that an understanding of TARP expression in nociceptive circuitry may reveal novel therapeutic targets, in that TARPs endow AMPARs with a unique pharmacology. For example, two antagonists have recently been developed that selectively block AMPARs associated with γ-8 (Gardinier et al, 2016; Maher et al, 2016). Development of other TARP-selective drugs may increase the resolution of AMPAR-targeted pain therapies and aid in treating the maladaptive aspects of pain while retaining the basic nociceptive signaling necessary for survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that an understanding of TARP expression in nociceptive circuitry may reveal novel therapeutic targets, in that TARPs endow AMPARs with a unique pharmacology. For example, two antagonists have recently been developed that selectively block AMPARs associated with γ-8 (Gardinier et al, 2016; Maher et al, 2016). Development of other TARP-selective drugs may increase the resolution of AMPAR-targeted pain therapies and aid in treating the maladaptive aspects of pain while retaining the basic nociceptive signaling necessary for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Negative modulation of AMPA receptor γ8 offers the possibility of selectively reducing excitatory transmission within brain circuits associated with epilepsy. Both Lilly/Cerecor and Janssen Research & Development have disclosed compounds targeting AMPA receptor γ8 …”
Section: Jnj‐55511118 and Analogsmentioning
confidence: 99%
“…JNJ-40411813 also displays binding to human 5HT 2A receptors in vitro (K b = 1.1 μmol/L). In a Ca ++ mobilization assay in human embryonic kidney cells transfected with human mGlu2, JNJ-40411813 had an EC 50 of 64 ± 29 nmol/L, and in vitro Ca ++ and [ 35 S]GTPgammaS assays demonstrated that JNJ-40411813 is >50-fold more selective for mGlu2 than other mGlu receptor members.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be achieved by identifying TARP-dependent AMPAR PAMs and a similar strategy has recently been successfully implemented by Lilly in their search for safer AMPAR antagonists for the treatment of epilepsy. [43] Positive emission tomography studies with a range of AMPAR modulators have indicated that different concentrations of potentiators are required to selectively activate the CNS regions associated with procognitive and undesired effects, suggesting a potential role of localized auxiliary proteins resulting in AMPAR complexes with different biophysical properties [44].…”
mentioning
confidence: 99%